2014
DOI: 10.1007/s10140-014-1230-4
|View full text |Cite
|
Sign up to set email alerts
|

High pitch, low voltage dual source CT pulmonary angiography: assessment of image quality and diagnostic acceptability with hybrid iterative reconstruction

Abstract: Increased use of CT Pulmonary angiography in suspected pulmonary embolism (PE) has driven research to minimize radiation dose while maintaining image quality and diagnostic accuracy. Following institutional review board approval, we performed a retrospective comparison study in patients with suspected PE. Patients were scanned using an ultra high pitch dual source technique (pitch=2.6) using 120 kV (SVCTPA) (n=54) or 100 kV (RV-CTPA) (n=52). SV-CTPA images were reconstructed using filtered back projection (SV-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 22 publications
0
8
0
Order By: Relevance
“…Theoretically, scanning could be controlled by increasing or decreasing the pitch factor, where the CTDI vol received by patients would be reduced as the pitch factor increased, but at the expense of image quality [34,35]. However, for high-end MDCT scanners, such as second or third generation dual-source CT, a high temporal resolution ensures a reasonable diagnostic performance even with a high pitch factor [36][37][38]. Modern scanners were developed to cover a wider beam collimation range per rotation of the CT X-ray tube.…”
Section: Discussionmentioning
confidence: 99%
“…Theoretically, scanning could be controlled by increasing or decreasing the pitch factor, where the CTDI vol received by patients would be reduced as the pitch factor increased, but at the expense of image quality [34,35]. However, for high-end MDCT scanners, such as second or third generation dual-source CT, a high temporal resolution ensures a reasonable diagnostic performance even with a high pitch factor [36][37][38]. Modern scanners were developed to cover a wider beam collimation range per rotation of the CT X-ray tube.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, thoracic contrast-enhanced CT can also observe the disease-caused conditions in the lung parenchyma, mediastinal pleura, or chest wall (5). The changes in the lung parenchyma associated with PTE include pulmonary infarction, pulmonary hemorrhage, mosaic perfusion, masses, atelectasis, or pleural effusion (18,19). In this study, subarachnoid atelectasis occurred in 7 patients (11.67%), pulmonary metastases occurred in 8 patients (13.33%), pleural effusions were observed in 6 patients (10%), mosaic perfusion area was observed in 2 patients (3.33%), pneumonia occurred in 5 patients (8.33%), while for 32 patients (53.33%) no substantial findings were observed.…”
Section: Discussionmentioning
confidence: 99%
“…A retrospective study of ultra-high-pitch dual-source CTPA in patients with suspected PE found that a reduced voltage (100 kV) compared to a standard voltage (120 kV) resulted in significantly reduced radiation dose, greater subjective image quality, and improved SNR and CNR. Diagnostic agreement between readers for the reduced voltage was very high (κ = 0.891) [83]. Iterative reconstructive algorithms can further reduce patients' radiation exposure [84].…”
Section: Ct Pulmonary Angiography For Pre-procedural Planningmentioning
confidence: 97%